Robert Mapplethorpe. (1st August 2013) - Shaw, Hannah
"Night Work, " spread between Alison Jacques's two venues along Berners Street, was a study in team- work and the fan base of everlasting fame. The curators, the New York alternative band Scissor Sisters, named after the sexual position of tribadism, recently used seven Robert Mapplethorpes as the artwork for their 2010 album release, whose title has now been extended to this group show.